The national health system in Portugal: from expansion to crisis between 1970 - Fernandes, A.; Burnett, S.; Major, M.; Figueiredo, M. (Revista de Ciências Empresariais e Jurídicas, 2016)
Purpose: The purpose of this article is to discuss the idea that governments should not take policy measures for the development and growth of National Health System (NHS) without taking into account their financial sustainability. Design/methodology/approach: This article is based on a review of existing theories, documents and statistics. findings: This article analyses the major developments in public health policy in Portugal between 1970 and 2012. It presents the measures that established the National Health Service (NHS) in 1976, signalling the start of an expansionary health policy that led to quality health care provision, but at the cost of very high spending. From 1990, governments have focussed on reducing public expenditure on health, due to growth-rates in this area outstripping increases in GDP. Paradoxically, despite this position, in practice, all the governments have increased the amount of infrastructure supporting the NHS, which in turn has been funded through public debt. This debt was extended in all areas of public administration and became unsustainable, obliging the Portuguese government to ask the European Commission for financial assistance in 2011. Due to the austerity measures imposed by lenders, for the first time since the creation of the NHS, there was a real reduction of public expenditure on health in 2011 and 2012.